A study of ethylene polymerization catalyzed by homogeneous and silsesquioxane supported Titanium(IV) complexes - Mehta, A; Tembe, G.; Parikh, P.; Mehta, G. (Polimery, 2013)
The synthesis and characterization of titanium(IV) complexes anchored on polyhedral oligomeric silsesquioxane (POSS) and cyclohexanediol (CHD) has been investigated and compared with their unsupported analogs. These complexes were employed as catalysts for polymerization of ethylene at high temperatures in combination with organometallic aluminum compounds as co-catalysts. The influence of various reaction conditions on polymerization was discussed. The polyethylene obtained was found to be linear and displayed narrow molecular weight distribution with Mw in the range of 600—1000. The polymer was also analyzed with 1H NMR, 13C NMR and FT-IR spectroscopic method which revealed a chain transfer reaction to aluminum. The unique low molecular weight PE formed in this reaction exhibits properties that have potential industrial applications in surface coating and ink formulations.